2022
DOI: 10.1080/21655979.2022.2060778
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Low-density lipoprotein receptor-related protein 1B (LRP1B) inhibits the progression of hepatocellular carcinoma cells by activating the endoplasmic reticulum stress signaling pathway

Abstract: Hepatocellular carcinoma (HCC) has a high recurrence rate and mortality rate even after surgery. Low-density lipoprotein receptor-related protein 1B (LRP1B) has proven to be involved in tumor development and progression of multiple malignancies. However, the function of LRP1B in HCC progression has not been fully elucidated. Thus, we conducted this study to explore the relationship between LRP1B and HCC. Bioinformatic analyses implied that LRP1B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…GPC6 (glypican 6) is involved in the regulation of cell growth and cell division [ 53 , 54 ]. LRP1B , which is a member of the low-density lipoprotein (LDL) receptor family, is involved in numerous cellular processes [ 55 , 56 ]. CTNNA2 , also known as catenin alpha 2, facilitates the binding of actin filaments and is involved in the regulation of neuron migration and the development of neuron projections [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…GPC6 (glypican 6) is involved in the regulation of cell growth and cell division [ 53 , 54 ]. LRP1B , which is a member of the low-density lipoprotein (LDL) receptor family, is involved in numerous cellular processes [ 55 , 56 ]. CTNNA2 , also known as catenin alpha 2, facilitates the binding of actin filaments and is involved in the regulation of neuron migration and the development of neuron projections [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] Meanwhile, low-density lipoprotein receptor-related protein 1B (LRP1B) is another member of the LDLR gene family, inducing HCC metastasis and drug resistance of doxorubicin and depressing the PERK-ATF4-CHOP pathway. [ 37 ] Additionally, microRNA-148a (miR-148a) prevents lung colonization of HCC, with real-time quantitative polymerase chain reaction (RT-qPCR) findings indicating that genes related to FA intake were upregulated in miR-148a KO mice. [ 38 ] ATP binding cassette subfamily A member 8, which has been established to regulate cholesterol efflux and HDL levels, is regulated by miR-374b-5p and impedes the metastasis of HCC.…”
Section: Lipid Metabolic Reprogramming In Hccmentioning
confidence: 99%
“…A study by Li et al [21] showed that high expression of LRP1B can mediate lipid metabolism of hepatocellular carcinoma cells. Zhen et al [22] discovered that LRP1B plays an imperative role in promoting hepatocellular carcinoma progression by regulating the PERK-ATF4-CHOP signalling pathway. However, there are few studies on LRP1B in TC, and further research should be carried out.…”
Section: Western Blotmentioning
confidence: 99%